PENGARUH KOMPETENSI GURU DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DENGAN MEDIASI MOTIVASI KERJA - 11.52.02.0153, Endriana Ambarwati (Jurnal Mahasiswa Pasca Sarjana, 2013)
Purpose of this study was to examine and analyze the effect of teacher competence and school leadership on teacher performance withmediation work motivation in SMP Negeri Sub Rayon 05 Semarang, total population of 161 respondents using a 5 point likert scale questionnaire. The result showed (1) Teacher competence has positive and significant effect on work motivation (2) Principal leadership does not effect on work motivation (3) Teacher competency do not effect the teachers performance (4) Principal leadership has positive and significant effect on teacher performance (5) Work motivation has positive and significant effect on teacher performance (6) The relationship of teacher competence directly effect the performance of the teacher so do not need the mediation of work motivation (7) Relationship principal leadership directly effects the teacher performance through the mediation of work motivation. Keywords : Teacher Competence, Principals leadership, Motivation, Teacher performance.